Identification of Criminogenic Needs for Property Crime Convicts in Correctional Institution Class IIB Pangkalan Bun - Sutra, Bahtiyar Mandala; Rahayu, Mulyani (Srawung: Journal of Social Sciences and Humanities, 2022)
This research is analyzed the factors that influence a person to commit a crime that is commonly known as criminogenic needs which focuses on property crime convicts in Correctional Institution Class IIB Pangkalan Bun. The objectives of this research are to provide an explanation of the criminogenic needs of convicts in the case of theft and to discuss the benefits of research results for determining the pattern of convicts development. This research focuses on criminogenic needs that can affect the repetition of criminal acts, with the basic concepts of Bonta and Andrews research in 2007, which explained about the risk, needs, and responsiveness. This research used a mixed methods approach. While, the research sampling process was conducted using a purposive sampling technique, that is using 59 convicts for theft cases. Data collection was conducted by several techniques, such as distributing questionnaires, interviews and literature studies. The data were obtained from the respondents'answers in the questionnaire which were processed using the SPSS version 25.0 program. The criminal record, educational and employment, financial, the relatives and family, drugs and alcohol, emotional and personality, criminal duration, and the perception of Correctional Institution can be concluded as factors for the criminogenic needs of property crime convicts in Correctional Institution Class IIB Pangkalan Bun. Based on these factors, these can used in determining the form of coaching policies given to convicts, then it is used to avoid the possibility of recidivism.